STRUKTUR TEKS MIKTO PADA CHANNEL YOUTUBE NAJWA SHIHAB KAJIAN WACANA KRITIS TEUN A. VAN DIJK - Widya Widya; Mahmudah Mahmudah; Muhammad Rapi (Fakultas Bahasa dan Sastra Indoensia, 2024)
In language studies there are studies that function to understand language in its use. This intends to help listeners and readers to understand the implied meaning in a text, especially in critical discourse studies. Teum A. Van Dijk divides the function of language into four namely ideology, domination, power, influence. The object of study in this analysis is a video entitled